Temporal dispositions of the future and school longevity in low income families - Maria José Braga Viana (Perspectiva, 2010)
This paper presents the results of two studies about a common issue: the conditions that allow the statistically improbable phenomenon of school longevity in low income families. More specifi cally, it seeks to identify in the socializing practices of these families a space for constitution of measures that support permanence in school among their children. I maintain that this would be one of the ways by which low income families can be present in the prolonged schooling of their children. Among the types of dispositions investigated I highlight temporal ones. In a recent study I studied seven cases of students in the College of Pedagogy at FaE/UFMG in 2002 and 2003, through interviews; these subjects were selected from a group of 120 hand written school biographies. Although it focuses on data from interviews, the analysis presented here also considers elements of these autobiographies, as well as the trajectories of two cases from a previous study. A general conclusion of these studies is that these families have an expanded perspective of the future – a position that is not typical among low income groups – expressed above all in the possibility for a better life for their children via schooling.